Rediscovery of the Philippine Bare Backed Fruit Bat (Dobsonia Chapmani Rabor) On Southwestern Negros Island, Philippines - Alcala, Ely L.; Paalan, Renee B.; Averia, Leonardo T.; Alcala, Angel C. (Silliman Journal, 2022)
Since its last sighting in the late 1960s, the Philippine are-Backed Fruit Bat was presumed extinct. Its recent discovery on southwestern Negros Island confirms the existence of the species, despite the animal's disappearance in their former habitat on Negros Island. The discovery of five individuals in Calatong forest is a new capture record for the species. This paper also discusses the behavior of the individuals in captivity and their habitat characteristics. Netting success is also discussed together with the capture success of other bat species. This study was made possible through a grant provided by the ASEAN Regional Centre for Biodiversity Conservation (ARCBC).